Revolutionizing grease formulation: Sustainable practices and thermal performance enhancement through waste transformer oil and advanced additives - Nor Amira Fatihah, Bashari; Mohd Aizudin, Abd Aziz; Miles, Nick; Muhammad Auni, Hairunnaja; Mohd Faizal, Ali (Semarak Ilmu Sdn. Bhd., 2025)
This research explores the formulation of sustainable and high-performance greases utilizing waste transformer oil (WTO) as a base material and incorporating additives such as molybdenum disulphide (MoS2), polytetrafluoroethylene (PTFE), and fumed silica. The study involves a meticulous process, including the pre-treatment of WTO, grease production, blending of additives, and thorough characterization. Various tests, including consistency, dropping point, oil bleeding, and FTIR analysis, provide comprehensive insights into the thermal stability, mechanical properties, and molecular composition of the formulated greases. The research contributes to advancing grease formulation practices, with a focus on sustainability and performance enhancement. The successful integration of waste transformer oil and additives demonstrates the potential for environmentally conscious lubrication solutions. This study provides a valuable foundation for future developments in the field.